Structural and technological analysis of typical aircraft parts and structures subject to manufacturing or repair using reverse engineering technologies - Kateryna Maiorova (Авіаційно-космічна техніка та технологія)
The subject of the study is the process of restoring destroyed or damaged components of aircraft equipment using reverse engineering (RE) methods, particularly in situations where design documentation is unavailable and the equipment requires urgent return to service. The aim is to justify the effectiveness of reverse engineering technologies for generating digital models and technical documentation under field conditions, as well as to systematize typical aircraft components based on their suitability for scanning and prototyping. The tasks include: identifying categories of aircraft object (AO) components that can be promptly restored on-site; analyzing types of damage for which RE methods are most appropriate; developing a classifier of AO components and assemblies based on their geometry, size, material, and restoration accuracy requirements; and formulating an algorithm for selecting optimal scanning and modeling methods. The methods used include structural and functional analysis of the geometry of typical aircraft parts, technical evaluation of the capabilities of optical and contact 3D scanning, generation of polygonal models, CAD modeling, mirror reproduction of paired elements, and systematization based on empirical observations and technical testing under mobile maintenance conditions. The following results were obtained: a detailed classifier of AO components and assemblies was developed, comprising 11 categories based on shape, presence of holes, rigidity, and structural complexity; typical damage types that can be repaired using RE methods were identified; the effectiveness of mirror scanning of symmetrical paired parts in the absence of original reference components was substantiated. Critical factors affecting scanning quality were established. Conclusions: the methodology presented in the article enables technically sound restoration of aircraft components using reverse engineering tools, even under field conditions, without the need for original design documentation. The proposed classifier facilitates rapid identification of the damaged part type and selection of suitable scanning and CAD modeling techniques. The method has proven effective for both aerodynamic elements and moving joints of the "shaft-in-hole" type, where a new compatible part can be created based on the less worn component.